Reduced Graphene Oxide/Polyvinyl Alcohol Nanofibers Fabricated by Electrospinning Technique as An Ideal Candidate for Organic Solar Cell Devices - Asriani Asriani; Iman Santoso (JPSE (Journal of Physical Science and Engineering), 2021)
Functionalization of rGO that previously obtained by chemical reduction using hydrazine hydrate, has been done by changing its morphology into nanofiber with electrospinning technique and using PVA as a polymer matrix. The rGO nanofibers that had been formed were then characterized using Fourier Transformation-Infra Red (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), and UV-Vis Spectrophotometer. FTIR spectroscopy confirmed the presence of C – C group and C = O group in nanofibers. SEM showed the change of nanofibers morphology which is marked by the increasing of fibres diameter and the hollow fibres become brighter. Furthermore, the effect of rGO concentration to nanofiber optical properties was confirmed by UV-Vis spectrophotometer. According to this characterization, the absorbance of rGO/PVA nanofiber is decreased due to increased rGO concentration. The detail of optical properties of rGO is studied through complex refractive index and dielectric constant in which Kramers-Kronig transformation is then employed to calculate complex refractive index and complex dielectric constant. From the data, the optical properties of rGO/PVA nanofibers indicating that rGO/PVA nanofibers can be applied as transparent electrode an organic solar cell devices.DOI: 10.17977/um024v6i12021p010